2021
DOI: 10.12688/gatesopenres.13357.1
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic COVID-19 in the elderly: dementia and viral clearance as risk factors for disease progression.

Abstract: Background: SARS-CoV-2 infected individuals ≥60 years old have the highest hospitalization rates and represent >80% fatalities. Within this population, those in long-term facilities represent >50% of the total COVID-19 related deaths per country. Among those without symptoms, the rate of pre-symptomatic illness is unclear, and potential predictors of progression for symptom development are unknown. Our objective was to delineate the natural evolution of asymptomatic SARS-CoV-2 infection in elders and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In this trial, 75% of participants received advanced respiratory support, which often occurs between 7 days and 10 days after symptom onset, and by which stage in the disease many patients who are immunocompetent will have developed endogenous antibody responses. 22 This could explain the overall results, including the effect observed in the prespecified immunodeficiency subgroup (Figure 4). Organ support-free days A, The ordinal scale includes death (in-hospital death, the worst possible outcome) and a score of 0 to 21 (the numbers of days alive without organ support) by trial group as the cumulative proportion (y-axis) for each trial group by day (x-axis), with death listed first.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this trial, 75% of participants received advanced respiratory support, which often occurs between 7 days and 10 days after symptom onset, and by which stage in the disease many patients who are immunocompetent will have developed endogenous antibody responses. 22 This could explain the overall results, including the effect observed in the prespecified immunodeficiency subgroup (Figure 4). Organ support-free days A, The ordinal scale includes death (in-hospital death, the worst possible outcome) and a score of 0 to 21 (the numbers of days alive without organ support) by trial group as the cumulative proportion (y-axis) for each trial group by day (x-axis), with death listed first.…”
Section: Discussionmentioning
confidence: 86%
“…For the convalescent plasma group, the median WHO score was 6 (required intubation and mechanical ventilation) and the IQR range was 3 (hospitalized but did not require oxygen therapy) to 7 (required ventilation plus additional organ support with vasopressors, kidney replacement therapy, or ECMO). For the no convalescent plasma group, the median WHO score was 5 (required noninvasive mechanical ventilation or high-flow oxygen) and the IQR was the combined 0- These findings also warrant further investigation of the hypotheses that benefit with convalescent plasma may be different early on in the illness, 22,23 and perhaps in patients with an impaired immune system who are unable to mount effective immune responses, including antibody responses. 23,24 The prespecified anti-SARS-CoV-2 antibody and SARS-CoV-2 polymerase chain reaction status subgroups were used to evaluate the hypotheses that the antibody-negative population and respiratory polymerase chain reaction-positive population may derive benefit from convalescent plasma therapy.…”
Section: Discussionmentioning
confidence: 88%
“…A total of 4357 records were identified in databases, registries, and other sources. There were 4 RCTs published in peer-reviewed journals [16][17][18][19] and 5 RCTs published as preprints [20][21][22][23][24] that were included. In addition, press releases were identified for 2 RCTs (the RECOVERY trial 8 and the Randomized, Embedded, Multifactorial Adaptive Platform Trial for Community-Acquired Pneumonia [REMAP-CAP] 25 ) but only the reported results from the RECOVERY trial 8 (NCT04381936) were included, stating 1873 deaths among 10 406 patients randomized (eFigure 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…The observations reported in the literature regarding a benefit with early high-titer plasma 1 administration in observational studies call for further analyses based on individual patient data such as the Continuous Monitoring of Pooled International Trials of Convalescent Plasma for COVID-19 Hospitalized Patients (COMPILE) project. 30 Fourth, except for 1 RCT with outpatients, 16 all patients were hospitalized with or without oxygen supplementation, indicative of moderate to critical COVID-19. The generalizability of the results to patients with milder COVID-19 is unclear.…”
Section: Limitationsmentioning
confidence: 99%